2002
DOI: 10.1093/brain/awf162
|View full text |Cite
|
Sign up to set email alerts
|

Change of chloride ion channel conductance is an early event of slow-to-fast fibre type transition during unloading-induced muscle disuse

Abstract: Disuse of postural slow-twitch muscles, as it occurs in hypogravity, induces a slow-to-fast myofibre type transition. Nothing is known about the effects of weightlessness on the resting membrane chloride conductance (gCl), which controls sarcolemma excitability and influences fibre type transition during development and adult life. Using the current-clamp method, we observed that rat hindlimb unloading (HU) for 1-3 weeks increased gCl in fibres of the slow-twitch soleus (Sol) muscle toward values found in fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
110
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(128 citation statements)
references
References 45 publications
18
110
0
Order By: Relevance
“…Studies carried out in rat and mouse muscles show that chloride conductance is higher in fast compared with slow muscle, and this is due to the higher level of expression of ClC1 in fast fibers, but also to the greater inactivation of ClC1 mediated by protein kinase C (PKC) phosphorylation in slow fibers (109,612). Several conditions that induce a fiber type transition are associated with the expected changes in ClC1 expression (611) and with changes in PKC-mediated inactivation (612). C) POTASSIUM CHANNELS.…”
Section: Ionic Channels and Membrane Excitabilitymentioning
confidence: 99%
“…Studies carried out in rat and mouse muscles show that chloride conductance is higher in fast compared with slow muscle, and this is due to the higher level of expression of ClC1 in fast fibers, but also to the greater inactivation of ClC1 mediated by protein kinase C (PKC) phosphorylation in slow fibers (109,612). Several conditions that induce a fiber type transition are associated with the expected changes in ClC1 expression (611) and with changes in PKC-mediated inactivation (612). C) POTASSIUM CHANNELS.…”
Section: Ionic Channels and Membrane Excitabilitymentioning
confidence: 99%
“…In mammalian skeletal muscle, innervation upregulates and denervation downregulates I IR expression (205), effects that appear to be secondary to activity-induced increases in [Ca 2ϩ ] i that stabilize IRK1 mRNA (540). Chloride channels also contribute to resting conductance, particularly in skeletal muscle, and their development appears to be dependent on innervation-induced electrical activity (236,293,482).…”
Section: ؉ -Gated Channelsmentioning
confidence: 99%
“…Previous studies have shown that immobilisation and unloading can result in a transition from slow to fast myofibres (Roy et al, 1996;Pierno et al, 2002). The transition occurs when the myofibres shift towards a myosin isoform with higher ATPase activity (Diffee et al, 1991).…”
Section: B L Mantle and Othersmentioning
confidence: 99%